Cleavable PEGylation: a strategy for overcoming the "PEG dilemma" in efficient drug delivery. (1st November 2017) - Fang, Yan; Xue, Jianxiu; Gao, Shan; Lu, Anqi; Yang, Dongjuan; Jiang, Hong; He, Yang; Shi, Kai
Abstract: To prolong the circulation time of drug, PEGylation has been widely used via the enhanced permeability and retention (EPR) effect, thereby providing new hope for better treatment. However, PEGylation also brings the "PEG dilemma", which is difficult for the cellular absorption of drugs and subsequent endosomal escape. As a result, the activity of drugs is inevitably lost after PEG modification. To achieve successful drug delivery for effective treatment, the crucial issue associated with the use of PEG-lipids, that is, "PEG dilemma" must be addressed. In this paper, we introduced the development and application of nanocarriers with cleavable PEGylation, and discussed various strategies for overcoming the PEG dilemma. Compared to the traditional ones, the vehicle systems with different environmental-sensitive PEG-lipids were discussed, which cleavage can be achieved in response to the intracellular as well as the tumor microenvironment. This smart cleavable PEGylation provides us an efficient strategy to overcome "PEG dilemma", thereby may be a good candidate for the cancer treatment in future.